ENVIRONMENTAL LAW ENFORCEMENT REGULATIONS REGARDING PRODUCER OBLIGATIONS IN WASTE MANAGEMENT IN INDONESIA - Hardi, Kresensia Angelica; Senastri, Dr. Ni Made Jaya; Wiryani, Dr. Made (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2024)
Waste management in Indonesia is still an unresolved matter that deserves to be studied. This research aims to analyze the sanctions arrangements and its legal implications for producer responsibilities in managing waste in Indonesia. This research constitutes normative research which combined with primary and secondary legal sources which are then analyzed qualitatively. There are several regulations that have a correlation with this research, which are The Waste Management Law of 18/2008, along with Government Regulation 81/2012 concerning the Handling of Household Waste and Similar Waste, Presidential Regulation 97/2017 regarding the National Policy and Strategy for Managing Household and Similar Waste, and Minister of Environment and Forestry Regulation 75/2019 outlining the Roadmap for Producers to Reduce Waste, are significant legislative measures in waste management. The findings of this research indicated that the waste management obligations by producers in Indonesia have been regulated in laws and regulations, but have not been provided with sanction arrangements, which have had legal uncertainty implications on environmental law enforcement related to the legal basis for applying sanctions and legal uncertainty about the jurisdiction of both the central and regional administrations in law enforcement against producer obligations in managing waste in Indonesia.